Effects of Corporate Governance Mechanisms on the Potential for Bankruptcy in Nepalese Commercial Banks - Purbey, Shweta; Bhurtel, Sushila; Nepal, Sushmita; Khadka, Swosti; Adhikari, Sudarshan; Shakya, Sarina (Nepalese Journal of Finance, 2025)
The study examines the effects of corporate governance mechanisms on the potential for bankruptcy in Nepalese commercial banks. Loan loss provision and non-performing loan are selected as the dependent variables. The selected independent variables are board size, board meetings, female directors, independent directors, audit committee and capital adequacy ratio. The study is based on secondary data of 13 commercial banks with 104 observations for the period from 2015/16 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance mechanisms on the potential for bankruptcy in Nepalese commercial banks. The study showed that board size has a positive impact on provision for loan loss and non-performing loan. It indicates that higher the board size, higher would be the provision for loan loss and non-performing loan. However, board meetings have negative impact on provision for loan loss and non-performing loan. It indicates that higher the board meetings, lower would be the provision for loan loss and non-performing loan. Similarly, female directors have negative impact on provision for loan loss and non-performing loan. It indicates that higher the female directors, lower would be the provision for loan loss and non-performing loan. Likewise, independent directors have negative impact on provision for loan loss and non-performing loan. It indicates that higher the independent directors, lower would be the provision for loan loss and non-performing loan. Further, audit committee size has a negative impact on provision for loan loss and non-performing loan. It indicates that higher the audit committee size, lower would be the provision for loan loss and non-performing loan. In addition capital adequacy ratio has a negative impact on provision for loan loss and non-performing loan. It indicates that higher the capital adequacy ratio, lower would be the provision for loan loss and non-performing loan.